Gp88/pgrn serum levels are associated with prognosis for oral squamous cell carcinoma patients - Greither, Thomas; Steiner, Tina; Bache, Matthias; Serrero, Ginette; Otto, Sven; Taubert, Helge; Eckert, Alexander W.; Kappler, Matthias (Biology, 2021)
Progranulin (PGRN)/GP88 is a growth factor that is expressed in a wide range of tumor tissues. The secreted form is involved in various biological processes including proliferation and in-flammation. In several tumor types, the serum GP88 level is associated with a patient’s prognosis; however, data for oral squamous cell carcinomas (OSCCs) have not yet been reported. We measured the serum GP88 levels in 96 OSCC patients by an enzyme immunosorbent assay (EIA) and correlated these data with clinicopathological parameters and patient outcomes. The GP88 levels in the serum of OSCC patients and healthy volunteers were comparable. In OSCC patients, the levels did not correlate with age, sex, or TNM status. In a Kaplan–Meier survival analysis, a serum GP88 level < 68 ng/mL was significantly associated with worsened survival (p = 0.0005, log-rank-test) as well as in uni-and multivariate Cox regression analyses (RR = 4.6 [1.6–12.9], p = 0.004 and RR = 4.2 [1.2–12.0], p = 0.008). This effect was predominant in OSCC patients older than 60.5 years (p = 0.027), while in younger patients no significant association between serum GP88 levels and prognosis could be observed. Altogether, lower serum GP88 levels are significantly associated with a worsened outcome for an OSCC and may be an interesting candidate for risk stratification during OSCC therapy.
CRIS-Team Scopus Importer:2021-06-04
Keywords: GP88; OSCC; Prognosis; Progranulin; Serum